0352 Prevalence of Marijuana Use versus Evidence-Based Treatments for Sleep and Relaxation. (12th April 2019) - Skobic, Iva; Apolinar, Gabriella R; Quan, Stuart F; Welty, Cody W; Haynes, Patricia L
Abstract: Introduction: Marijuana is often used to manage insomnia and anxiety symptoms, even though efficacious, evidence-based treatments (EBTs) are available. Marijuana may provide short-term sleep and relaxation benefits, followed by rapid habituation and worsening of symptoms. We compared the prevalence of marijuana use for sleep/relaxation to the use of EBTs in a large sample of recently unemployed individuals. Methods: Assessing Daily Activity Patterns through Occupational Transitions (ADAPT) is a longitudinal study examining linkages between job-loss, sleep, obesity, and mental health outcomes. We examined cross-sectional data from 513 participants of the ADAPT phone screen interview who reported recent use of sleep aids or treatments for sleep/relaxation problems. EBT was defined as Cognitive Behavioral Therapy for Insomnia (CBT-I), Ambien, and Benzodiazepines. A two-sample test of proportions was conducted to determine difference in prevalence of marijuana versus use of EBTs. Sensitivity analysis redefined EBTs as including tricyclic antidepressants, a commonly-prescribed but non-evidence-based treatment for insomnia. Results: Our analysis indicated a trend for higher prevalence of marijuana use (18%, n=92) than use of EBTs (14%, n=74; difference =.04, p=.08). After inclusion of tricyclic antidepressants, prevalence of use of EBTs (25%) was significantly higher than of marijuana (p=.006), but marijuana remained the single most common treatment for sleep/relaxation. Only 4% of our sample received CBT-I (n=2, difference=.18, p < .0001), 4% used Ambien (n=22, difference=.14, p < .0001), 11% used Benzodiazepines (n=58, difference=.07, p=.002), and 11% used tricyclic antidepressants (n=56, difference=.07, p=.002). Conclusion: Recently unemployed individuals are more likely to use marijuana than any one evidence-based treatment for sleep/relaxation. Job loss confers occupational and economic disparities that may contribute to barriers to EBT access for sleep/relaxation. Given marijuana's fragmented legality and the paucity of empirical evidence regarding its long-term efficacy as a sleep/relaxation aid, more research is needed into the economic, medical, and personal factors influencing individuals' decisions to use marijuana versus EBTs, as well as the long-term effects of marijuana for sleep/relaxation. Support (If Any): #1R01HL117995-01A1